Peran Komunikasi Antarbudaya Tour Guide dalam Meningkatkan Pengalaman Wisatawan di Bali. - Julita Mustika; Rama Buci Wiltar; Ratu Jelita; Rizky Putry Nelsya; Roxanne Tambunan; Selvira Rani; Hagi Julio Salas (Komsospol, 2025)
This research explores the role of intercultural communication performed by tour guides in enhancing tourist experiences in Bali. The study is grounded in the discipline of communication studies, particularly in the field of intercultural communication, where tour guides are positioned as cultural mediators who bridge interactions between tourists and local communities. The topic was selected because the effectiveness of communication between guides and tourists from diverse cultural backgrounds determines satisfaction, loyalty, and destination image. Using a descriptive qualitative method with field research, data were collected through in-depth interviews, observations, and documentation involving certified tour guides and tourists. Guided by the Anxiety/Uncertainty Management Theory (Gudykunst, 1991) and Face Negotiation Theory (Ting-Toomey, 1999), the study examines how communication competence reduces uncertainty, manages cultural differences, and maintains mutual respect. The findings indicate that tour guides in Bali not only deliver information but also serve as storytellers and cultural interpreters who create meaningful and emotionally engaging experiences. They demonstrate cultural and religious sensitivity by adjusting narratives and behavior according to tourists’ backgrounds, thus fostering inclusive and harmonious interactions. The research contributes theoretically by reaffirming the significance of intercultural communication in tourism contexts and practically by emphasizing the need for continuous training in language, empathy, and cultural adaptation. Ultimately, effective intercultural communication by tour guides enhances satisfaction and strengthens Bali’s image as a welcoming and culturally rich international destination.